SECONDARY SCHOOL TEACHERS’ KNOWLEDGE AND PRACTICES ABOUT CONSTRUCTIVE FEEDBACK: EVIDENCE FROM KARACHI, PAKISTAN - Rabia Aslam; Najmonnisa Khan (Jurnal Cakrawala Pendidikan, 2021)
Teachers’ knowledge, conceptualization and actual practices in the classroom influence students’ academic performance. The present study sought to determine the existing practices and knowledge of teachers about constructive feedback, and to find how the knowledge of teachers would predict teachers’ feedback practices in classroom.  A quantitative approach with survey research design was adopted to collect the data from the respondent through feedback knowledge questionnaire. The participants of the study were 396 secondary schools teachers of Karachi, Pakistan which were selected randomly from the population. Findings show that the teachers have good knowledge about providing constructive feedback as all the mean values of the constructs were in the range of acceptance (3.61-4.18). However they are not utilizing this knowledge in their daily teaching, as evidence from the descriptive analysis shows that majority teachers (69%) are taking more than a week time to provide feedback, and it is mostly in the form of verbal comments (64.1%) or just only tick or cross mark on students’ work (76.2%). That is the reason that insignificant results were found between teachers’ practices and their perception with very week negative correlation and effect size was also found negligible. Professional trainings are recommended to overcome this contradiction.